MENILIK KETEPATAN WAKTU PELAPORAN KEUANGAN DITINJAU DARI PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Melissa Ramadhani Azis (ITB AAS INDONESIA Surakarta, 2021)
Timeliness of financial reporting is a condition in which issuers submit their financial reports to the IDX according to the time limit determined by the OJK, which is March 31, unless otherwise determined by the OJK. Examine and analyze the relationship between profitability and timeliness of financial reporting which is moderated by company size in terms of the purpose of the research. There were 16 samples from 29 food and beverage companies listed on the IDX during 2018-2020 which were obtained with the help of purposive sampling. The analytical technique used is Partial Least Square (PLS) with the SmartPLS version 3.0 tool. The research results prove that profitability does not affect the timeliness of financial reporting, moderated profitability by company size also does not affect the timeliness of financial reporting. There are a few components that can affect the presentation of financial statements as quickly as possible to the public.